Trichoscopic signs in systemic lupus erythematosus: a comparative study with 109 patients and 305 healthy controls - P. Suchonwanit (2020)
© 2019 European Academy of Dermatology and Venereology Background: Hair and scalp involvement in systemic lupus erythematosus (SLE) can manifest as scarring alopecia, non-scarring alopecia or scalp/hair shaft changes without apparent hair loss. While trichoscopic signs in chronic cutaneous lupus are well established, data on SLE patients with normal-looking or non-scarring scalp are limited. Objectives: To investigate trichoscopic features of SLE patients without chronic cutaneous scalp lesions and compare the findings with normal controls, as well as determine which feature associates with systemic disease. Furthermore, we aim to explore different clinical presentations of the scalp in SLE patients and their association with disease activity. Methods: Trichoscopic photographs were taken from patients and healthy controls and evaluated by one blinded hair specialist. For SLE patients, their clinical presentations and evaluations for cutaneous, extracutaneous involvement; SLE Activity Index 2000 (SLEDAI-2K) score were documented. Results: Of 109 SLE patients and 305 healthy controls were included. Hair shaft changes were significantly more common in SLE and associated with higher SLEDAI-2K (P < 0.05). The most common feature was prominent arborizing blood vessels (60.6% vs. 18.4%, P < 0.001), followed by thick arborizing blood vessels (57.8% vs. 10.2%, P < 0.001), black dots (47.7% vs. 2%, P < 0.001), brown scattered pigmentation (5.5% vs. 0.7%, P = 0.005) and blue–grey speckled pigmentation (44% vs.0.3%, P < 0.001). When hair loss is diffuse and severe, there were associations with haematologic (P = 0.002) and renal involvement (P = 0.027 for proteinuria > 500 mg/day, P = 0.004 for proteinuria > 1 g/day). Conclusions: Trichoscopic examination is a valuable tool for SLE diagnosis and monitoring. Severe diffuse non-scarring alopecia most likely indicates active disease.